Fatal Cases of Gestational Trophoblastic Neoplasia in a National Trophoblastic Disease Reference Center in Dakar Senegal - Mamour Gueye, MD; Mame Diarra Ndiaye-Gueye; Serigne Modou Kane Gueye, PhD; Jean Charles Moreau, PhD (Global Health and Education Projects, Inc., 2016)
Objectives: The objectives of this study were to analyze deaths after gestational trophoblastic neoplasia and to determine the factors of treatment failure. Methods: This is a retrospective study in Aristide Le Dantec teaching Hospital in Dakar, Senegal, between 1 January 2006 and 31 December 2014. We took into account socio-epidemiological characteristics of patients, initial diagnosis, time between uterine evacuation and admission, time to onset of gestational trophoblastic neoplasia (GTN), treatment received (deadlines, protocols), difficulties experienced in the diagnosis and the initiation of treatment and survival. Results: In total, 1044 patients were admitted during the study period; 164 cases of GTN were diagnosed (15.7%); and 21 deaths occurred leading to a specific lethality of 12.8%. The average age was 30 years. Almost all patients (n = 18; 85.7%) had low income or no income. Eight out of 21 patients (38.1%) were seen in our department after GTN onset. The mean time to onset of GTN of all patients was 22.1 weeks. For 66.6%, histology was not available; the diagnosis of hydatidiform mole was made on the clinical history and sonographic features and GTN on human chorionic gonadotrophin (hCG) evolution and ultrasound findings. None of the patients had regular chemotherapy due to financial reasons. Patients who died within 3 months after diagnosis had metastatic tumors (7 of 21). All these women had resistance to treatment or progressed after three courses of chemotherapy. Ten of the 12 women with high-risk GTN were not treated with multi-agent chemotherapy (EMA-CO) for purely financial reasons. Conclusion and Global Health Implications: The high incidence and mortality require a profound reorganization of our health system and a high awareness of practitioners to refer to time or to declare all suspected cases of hydatidiform mole or gestational trophoblastic neoplasia. Key words: Gestational • Trophoblastic Neoplasia • GTN • Outcome • Death • Senegal Copyright © 2016 Gueye et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.